Factors Correlated With The Incidence Of Diarrhea In Infants with Nola J.Pender Approach in Emergency Room of RSUD Ruteng - Susana S. Sukut; Yuni S. Arief; Nuzul Qur'aniati (Pediomaternal Nursing Journal, 2016)
Introduction : Diarrhea is a condition that is characterized by frequent bowel movements ( > 3 times each day) along with decrease in the form of stool (greater looseness of stool), with or without blood and mucus. This study aimed to determine the factors correlated with the incidence of diarrhea in infants in emergency room of RSUD Ruteng.Methods : The design used in this research was descriptive analysis with cross-sectional approach. The population was the parents of children under five years old who suffered from diarrhea and visited emergency room of RSUD Ruteng with 40 children as the sample. This study used purposive sampling technique. The independent variables were perceived benefit, perceived barrier, perceived self-efficacy, activity-related affect, commitment, mother’s knowledge, immediate competing demands and preferences, and situational factors, while the dependent variable was the incidence of diarrhea. The data were collected by questionnaires and medical records. This study used linear regression analysis.Result : The result showed that relationship between knowledge with diarrhea(p=0.004), relationship between environmental hygiene with diarrhea (p=0.006), Jurnal Pediomaternal 231 Vol. 3 No. 2 April—Oktober 2015 relationship between action benefit with diarrhea (p=0.009), relationship between perceived barriers with diarrhea (p=0.430), relationship between commitment with diarrhea (p=0.006), relationship between desire to compete with diarrhea (p=0.007), relationship between self-efficacy with diarrhea (p= 0.007), relationship between attitudes towards activities with diarrhea (p=0.009)Discussion: The research proved that independent variables were factors influencing diarrhea in infants. Suggestion was addressed to future reaserch which would be interseted in conducting such study, but in different methdos, for instance in parents’ knowledge and attitude towards oralite giving for children with diarrhea